Biosynthesis of anti-leishmanial natural products in callus cultures of Artemisia scoparia. Issue 1 (4th December 2019) - Yousaf, Reema; Khan, Mubarak Ali; Ullah, Nazif; Khan, Imdad; Hayat, Obaid; Shehzad, Muhammad Aamir; Khan, Irfan; Taj, Faqeer; Ud Din, Nizam; Khan, Asghar; Naeem, Ijaz; Ali, Huma
Abstract: Clinically, available synthetic chemotherapeutics in the treatment for leishmaniasis are associated with serious complications, such as toxicity and emergence of resistance. Natural products from plants can provide better remedies against the Leishmania parasite and can possibly minimize the associated side effects. In this study, various extracts of the callus cultures of Artimisia scoparia established in response to different plant growth regulators (PGRs) were evaluated for their anti-leishmanial effects against Leishmania tropica promastigotes, followed by an investigation of the possible mechanism of action through reactive apoptosis assay using fluorescent microscopy. Amongst the different callus extracts, higher anti-leishmanial activity (IC50 :19.13 µg/mL) was observed in the callus raised in-vitro in the presence of 6-Benzylaminopurine (BA) plus 2, 4-Dichlorophenoxyacetic Acid (2, 4-D) at the concentration of 1.5 mg/L, each. Further, the results of apoptosis assay showed a large number of early-stage apoptotic (EA) and late-stage apoptotic (LA) cells in the Leishmania under the effect of callus extract grown in-vitro at BA plus 2, 4-D. For the determination of the potent natural products in the callus extracts responsible for the anti-leishmanial activity, extracts were subjected to Gas chromatography-mass spectrometry (GC-MS) for the metabolite analysis. Nonetheless, higher levels of the metabolites, such as nerolidol (22%), pelletierine (18%), aspidin (15%) and ascaridole (11%) were detected in the callus grown in vitro at BA plus 2, 4-D (1.5 mg/L, each). This protocol determines a novel method of production of anti-leishmanial natural products through callus cultures of A. scoparia, a medicinal plant.